Impact Of Building Envelope Modifications On Thermal Performance Of Classrooms In Typical Schools In Hot Arid Climate Of Oman - Ali, Alsaadi Mutaib Ibrahim (2024)
This study addresses a critical oversight in environmental design and energy conservation for typical government schools in Muscat, Oman, which grapples with inadequate adaptation to its hot-arid climate, leading to a heavy reliance on mechanical systems for temperature control. This research examined the thermal performance of building envelope elements and their impact on indoor air temperature by modifying the exterior wall, roof, glazing type, window area, and orientation. Simultaneously, it provided nuanced design recommendations for optimal thermal comfort. The study was conducted in two pivotal phases. The first phase involved fieldwork measurements in three secondary schools, providing a real-world snapshot of existing thermal conditions within such buildings. The second phase employed computer simulations using Design-Builder software to replicate field measurements, explore hypothetical scenarios and modify building envelope elements. Winter indoor temperatures recorded in the fieldwork phase ranged from 24.2oC to 24.8oC, ensuring a baseline understanding of the existing conditions. In contrast, summer temperatures spanned from 32.7oC to 33.3oC, illustrating the considerable temperature fluctuations of typical schools. The recorded field measurements and the simulation results revealed a close alignment of minimal differences of less than 2oC, highlighting the study's credibility and strengthening the validity of the proposed design recommendations.